Pelatihan Pembuatan Lubang Resapan Biopori (LRB) dan Pupuk Cair Limbah Cucian Beras di Desa Wonotirto, Kecamatan Karanggayam, Kabupaten Kebumen - Nardiansyah, Afrie; Rahmawati, Aulia; Saputra, Dimas Andi; Septyningsih, Nurmila; Tofik, Akhsan; Musyafa, Nasyith; Wahyuni, Endah; Winarsih, Windu; Syahputra, Dimas Nur Alim; Hayati, Tuti Nur; Anwar, Saeful; Musarofah, Zul (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Environmental problems continue to grow and become more complex over time. One of the problems that occurs is the number of puddles on village roads due to increasingly low water absorption space. In this case, based on a survey in Wonotirto Village, another problem arises, namely that waste processing, especially organic waste, is still not maximally utilized. In general, people in Wonotirto Village dispose of organic waste in their yards and burn it. The approach method used to find out the problems in this service activity includes interviews and observations in the field. The training on making biopore infiltration holes (BIH) can be used as a medium for making organic fertilizer. That way this program aims to educate and increase public understanding of groundwater infiltration holes and the use of organic waste for the environment. Community service activities in the form of socialization and training in making Biopore Infiltration Holes (BIH) and utilizing organic waste as fertilizer. The results of the activity were the installation of two biopore infiltration holes at Wonotirto Village Hall and training in making liquid fertilizer from leftover rice washing water. Making Biopore Infiltration Holes (LRB) can increase the amount of water infiltration and get the benefits of organic waste to fertilize the soil. During the rainy season, Biopore Infiltration Holes (BIH) can prevent flooding and can accommodate water sources. Making liquid fertilizer from leftover rice washing water can utilize household liquid waste and save money on fertilizer purchases.